The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/2059700220947194
|View full text |Cite
|
Sign up to set email alerts
|

Interval-censored survival analysis of mild traumatic brain injury with outcome based neuroimaging clinical applications

Abstract: Objective The purpose of this study was to assess the relationship between MRI findings and clinical presentation and outcomes in patients following mild traumatic brain injury (mTBI). We hypothesize that imaging findings other than hemorrhages and contusions may be used to predict symptom presentation and longevity following mTBI. Methods Patients (n = 250) diagnosed with mTBI and in litigation for brain injury underwent 3T magnetic resonance imaging (MRI). A retrospective chart review was performed to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 76 publications
(90 reference statements)
0
9
0
Order By: Relevance
“…The duration of LOC in women, but not men, was positively correlated with loss of balance, poor coordination, fatigue, and overall vestibular impairment score on the NSI in a study comparing male and female veterans [22]. Additionally, LOC was associated with balance problems, fatigue, and headache; interestingly, every patient with LOC in this study reported headache [25]. In military personnel, LOC was associated with greater levels of plasma interleukin (IL)-6, a pro-inflammatory cytokine, and greater self-reported pain levels [20].…”
Section: Physical Symptomsmentioning
confidence: 52%
See 2 more Smart Citations
“…The duration of LOC in women, but not men, was positively correlated with loss of balance, poor coordination, fatigue, and overall vestibular impairment score on the NSI in a study comparing male and female veterans [22]. Additionally, LOC was associated with balance problems, fatigue, and headache; interestingly, every patient with LOC in this study reported headache [25]. In military personnel, LOC was associated with greater levels of plasma interleukin (IL)-6, a pro-inflammatory cytokine, and greater self-reported pain levels [20].…”
Section: Physical Symptomsmentioning
confidence: 52%
“…The presence and duration of LOC are associated with cognitive deficits after mTBI. LOC was associated with cognitive deficits and slow recovery of cognitive function [25]. Among military personnel and civilian contractors, longer duration of LOC was associated with a greater decline in accuracy on the Automated Neuropsychological Assessment Metric (ANAM), which measures reaction time, learning, and memory, between baseline and post-injury tests [11].…”
Section: Cognitive and Memory Deficitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Brain volume abnormalities correlated with acute measures of injury (including greater duration of posttraumatic amnesia and lower GCS score) and presence of diffuse axonal injury (Brezova et al, 2014). Vanier et al (Vanier et al, 2020) divided a sample of mild TBI patients into those with and without MRI brain abnormalities, including hippocampal atrophy or asymmetry based on NeuroQuant R analyses; patients with MRI abnormalities had slower recovery from balance and cognitive deficits. In a study of pediatric patients with TBI, Wright et al found that increased volumes of white matter hyperintensities measured by NeuroQuant R correlated with decreased cognitive processing speed (Wright et al, 2020).…”
Section: Validity Of Neuroquantmentioning
confidence: 99%
“…These include multiple studies that found that NeuroQuant V R is reliable for measuring brain volume in normal subjects, patients with TBI, and other neuropsychiatric patients 8,[29][30][31][32][33][34][35] and valid for assessing brain volume in patients with TBI. 4,5,8,12,16,19,25,33,[35][36][37][38][39][40][41] Neuroquant V R automated brain MRI segmentation. The brain MRI grayscale images for each patient and NeuroGage V R normal control V R were uploaded to the NeuroQuant V R server, which processed and analyzed the brain imaging data.…”
Section: Brain Imaging and Volume Measurementmentioning
confidence: 99%